Incorporating Local Craft in Chemical Processes to Enhance Students’ Comprehension of Concepts and Interest in Chemistry - Olude, Sylvester Adebisi; Oludipe, Olajumoke; Saibu, Sakibu; Ademola, Ibukunolu; Owolabi, Tunde; Akintoye, Hakeem (Journal of Education and Learning Research, 2025)
This study investigated the integration of local craft activities involving chemical processes into chemistry teaching as a strategy to address challenges in schools, where inadequate resources and equipment often hinder effective instructional delivery. A non-equivalent pre-test and post-test quasi-experimental design was employed. Using simple random sampling, two senior secondary schools in Badagry, Lagos State (District V), were selected, with two intact classes comprising 68 for the experimental group and 74 students for the control group, making a total of 142 respondents. The research instruments included a Chemistry Achievement Test (CAT) and Chemistry Students Interest Questionnaire (CSIQ), both validated and subjected to reliability testing via a test-retest method, yielding coefficients of 0.80 and 0.78, respectively. Findings revealed that students demonstrated better comprehension when working with locally available materials [F(1,198)=19.82; p<0.05] in schools. Additionally, their interest in pursuing chemistry courses increased [F(1,198)=13.04; p<0.05]. The study concludes that integrating local craft activities into chemistry instruction showcases real-life applications of chemical processes, enhancing student comprehension and a deeper appreciation of the subject. The study recommends that workshops and conferences should be put in place to up-date teachers’ knowledge and make available necessary materials for the smooth running of the programme.